2010
DOI: 10.5205/reuol.980-7143-1-le.0402201043
|View full text |Cite
|
Sign up to set email alerts
|

Knowing yourself: women opinions about menopause and climacteric

Abstract: Objective: to know women’s opinion about climacteric and menopause attended at a Reproductive Health Center. Methodology: this is a descriptive-exploratory study, from qualitative approach, performed by 50 women from 45 to 59 years-old who answered a semi-structured interview, after the project has been approval by the Ethics Committee of the Federal University of Rio Grande do Norte under protocol number 031/2008. A technique of analysis of content was used on data collected. Results: 84% of women had heard a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another study [16], in the city of Natal, Rio Grande do Norte, found a low level of education. However, 64% of the sample reported having income greater than two minimum wages.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [16], in the city of Natal, Rio Grande do Norte, found a low level of education. However, 64% of the sample reported having income greater than two minimum wages.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies are still restricted on the factors that interfere with sleep patterns in postmenopausal women, and its possible consequences on quality of life [20][21].…”
Section: Sleep Disorders Versus Lifestylementioning
confidence: 99%